2019
DOI: 10.21272/mmi.2019.1-05
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management Efficiency of GCC Countries: Linking Between Composite Index of Environmental Performance, Socio-Political and Economic Dimensions

Abstract: This paper summarizes the arguments and counterarguments within the scientific discussion on the issue of environmental performance. The investigation of the topic of the Composite Index of Environmental performance (CIEP) in the paper is carried out in the following logical sequence. The research is focused on the relationship between the composite index of environmental performances and the sociopolitical and economic elements of countries. Systematization literary sources and approaches for solving the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Studies on environmental performance/quality and economic growth show inconclusive results. Many studies support a positive association between environmental performance and economic growth 8–13. On the contrary, a negative association between environmental quality and growth or openness has been also supported by several studies 9,12,14,15.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies on environmental performance/quality and economic growth show inconclusive results. Many studies support a positive association between environmental performance and economic growth 8–13. On the contrary, a negative association between environmental quality and growth or openness has been also supported by several studies 9,12,14,15.…”
Section: Introductionmentioning
confidence: 89%
“…Contrary to previous studies exploring the linkage between environmental performance and economic growth using a linear model,8–10 the current study used a non-linear model based on the PSTR model proposed by Hua et al 13. This model assumes that the relationship between EPI and economic growth may be non-linear, exhibiting a threshold effect in the EPI-growth relationship.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that national culture, economic development, and population growth would significantly influence environmental performance directly. The contribution of Dkhili and Dhiab (2019) concluded that the control variables (size, risk, and sector) do not moderate the relationship between social responsibility and financial performance. For Morosini et al (1998), the study of environmental performance is materialized by cultural values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…relationships between the political regime and the sustainable development of the agricultural sector in the economy. Thus, many scientists study the impact of the democracy level on the macroeconomic stability of the country Yevdokimov et al, 2018;Dkhili, 2018;Dkhili & Dhiab, 2019), economic development (Baklouti & Boujelbene, 2018;Kim & Heshmati, 2019;Acemoglu et al, 2019), analysing the development of economic sectors in the aggregate. Another group of scientists, on the contrary, is engaged in analysing the drivers regarding the sustainable development of particular sectors of the economy, including the agricultural sector (Prasad et al, 2017;Li et al, 2018;Altieri, 2018;Vasylieva et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%